2014
DOI: 10.1016/j.pediatrneurol.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprognostication After Pediatric Cardiac Arrest

Abstract: BACKGROUND Management decisions and parental counseling after pediatric cardiac arrest depend on the ability of physicians to make accurate and timely predictions regarding neurological recovery. We evaluated neurologists and intensivists performing neuroprognostication after cardiac arrest to determine prediction agreement, accuracy, and confidence. METHODS Pediatric neurologists (n = 10) and intensivists (n = 9) reviewed 18 cases of children successfully resuscitated from a cardiac arrest and managed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…29 Neurological clinical evaluation appears to be the main diagnostic tool when dealing with the probability of brain damage after cardiac arrest. This has been previously stated in other studies, [30][31][32][33] reflecting the difficulty of managing these patients after such a critical life-threatening event. Our results state that there is no common protocol that deals with managing these patients, trying to assess their outcome and establishing their follow-up.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…29 Neurological clinical evaluation appears to be the main diagnostic tool when dealing with the probability of brain damage after cardiac arrest. This has been previously stated in other studies, [30][31][32][33] reflecting the difficulty of managing these patients after such a critical life-threatening event. Our results state that there is no common protocol that deals with managing these patients, trying to assess their outcome and establishing their follow-up.…”
Section: Discussionsupporting
confidence: 59%
“…Once brain damage is suspected, several neurological sequelae have been described, with no clear trend towards an specific brain injury. 31,33,34 Follow-up of these patients, has shown that partial to complete recovery of these findings is registered in the longterm evolution of many patients. Pediatric brain damage, when not extreme, still holds some margin of recuperation, and 1 year after cardiac arrest, even the majority of those who had worsen their neurological scales, showed some improvement.…”
Section: Discussionmentioning
confidence: 90%
“…(15, 1722) Additionally, when neurologists and intensivists predict neurobehavioral outcomes from pediatric cardiac arrest cases, the addition of EEG data significantly improves prognostication accuracy. (23)…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations into the capabilities of clinical features, laboratory markers, imaging characteristics and electrophysiological testing have yielded mixed results in children (2, 3). Adult data is often more robust and has led to consensus statements regarding prognostication in survivors of cardiac arrest (4, 5), whereas no current analogue exists for children.…”
Section: Introductionmentioning
confidence: 99%